Synthesis and Characterization of CdS Nanoparticle and Measurement of Conductivity of Different Sample - Salunke Pooja; Jain Preeti (International Journal of Research in Chemistry and Environment (IJRCE), 2015)
The Cadmium Sulphide nanoparticle is a semiconductor material belongs to the group II-VI, having a direct band gap of 2.42 eV. CdS is a versatile material with unique properties like optical, electronic, thermal, etc, it has a wide range of applications in sensors, biomedical devices, light emitting devices, etc, in the present work, the preparation of CdS nanoparticles were done by using chemical precipitation and green chemical route and characterization are done through UV-Visible spectroscopy is used for particle size determination obtained around 3-10 nm and FTIR is used for identification of compounds by matching spectrum of a sample compound. The measurement of conductivity is done by TDS digital meter.